Causes and Effects of Water and Environmental Pollution: A Way Forward - Dr. Tahira Mumtaz; Dr.Ammara Tariq Cheema; Rabia (Journal of Political Studies, 2023)
Pollution is not a new marvel, yet it is still one of the world's most prominent human issues, with its driving reasons for sickness and demise. Human activities through urbanization, industrialization, and mining are major factors of worldwide Pollution. Both advanced and developing states share this impulse, even though cognizance and flexibility in advanced states primarily affect the security of their current situation. Although worldwide attention regarding Pollution, the effect is as yet felt because of its drawn-out adverse consequences. All kinds of pollution are discussed in this study. The majority of researchers emphasize the study of water pollution. The fundamental changes it makes to humans, animals, plants, soil, and the environment as a whole are what give it significance. The study discusses water pollution caused by dumping solid, carbon-based, and liquid materials into lakes and waterways that comprise toxic chemicals like lead, mercury, and metals. One of the most significant kinds of pollution from nuclear activity is harmful pollution, which occurs when materials flow into the water and become toxic and polluting substances. The majority of factories do not use pesticides and fertilizers to industrial drainage regulations, so the waste reaches the water. Additionally, home waste outflows contribute to water pollution. In addition, it focuses on the most significant causes of groundwater pollution and the stages of its usage and distillation, highlighting hygiene sources as the most significant sources of water pollution.